Per pill price differences across therapeutic categories: a study of the essential drug brands marketed by multinational and local pharmaceutical companies in Bangladesh - Kabir, Eva Rahman; Chowdhury, Nishat (© 2009 Academic Journals, 2016)
This article was published in African Journal of Marketing Management [© 2009 Academic Journals] and the definite version is available at : http://www.academicjournals.org/journal/AJMM/article-full-text-pdf/42CAE062138 The article website is at: http://www.academicjournals.org/journal/AJMM